Vom Fremdverständnis zum Eigenverständnis: Kontrastive Linguisitik und Glottodidaktik - Schwenk, Hans-Jörg (Glottodidactica, 2011)
The present paper deals with the relationship between contrastive linguistics on the one hand and foreign language teaching on the other hand, more precisely, with the influence exerted by the first on the latter. It goes without saying that a teacher who teaches his mother tongue is expected to teach it as completely and correctly as possible. Yet the complete and correct teaching of any language depends on the teacher’s complete and correct knowledge of the given language and, comes to that, his awareness of this knowledge. It could be shown and proven on various examples that this aim can only be reached by the way of analyzing an other / a foreign language and comparing it with the language / the mother tongue to be teached, that, as much as paradoxical this may sound, self-understanding quite often needs the understanding of the other.